PULSATIONAL ACTIVITY OF THE SMALL–AMPLITUDE CEPHEID POLARIS (α UMi) IN 2018-2019 - Usenko, I. A.; Miroshnichenko, A. S.; Danford, S.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2019)
We present the results of an analysis of 20 spectra of α UMi (Polaris) obtained in September 2018 – January 2019 using 0.81m telescope of the Three College Observatory (TCO), North Carolina, USA. Frequency analysis displays an increase of the pulsational period up to 3.68 min in comparison to the August - December 2017 - January - May 2018 observational sets, and it come to 3.973216 days. The systemic velocity (γ – velocity) is equal to −11.75 kms −1 . The radial velocity amplitude rose to 3.50 kms −1 and actually returned to the previous values of 3.43, 3.31, and 3.81 kms −1 , respectively, found from the August - December 2016, January - March 2017 and August - December 2017 sets. The radial velocity’s amplitude growth tendency still remains. The average T eff = 6051±22 K shows a growth toward the value found from the 2005 – 2007 observational sets and probably has a tendency toward the T eff growth. The joint TCO and Hermes radial velocity measurements during the last four years show the changes of Polaris’ pulsational amplitude.